Optimization of an ac-dc transfer step-up scheme - Di Lillo, Lucas Daniel (2007)
A set of statistical tools is proposed for the optimization of an alternating current-direct current voltage or current transfer step-up scheme. These tools are used to remove standards with level dependence and instabilities and to discard unusual measurements with the aim of minimizing the uncertainties. The method was applied to the new Instituto Nacional de Tecnologia Industrial current step-up. © 2007 IEEE.